Effect of rice straw silage treated with rumen microbes of buffalo on digestibility and ecosystem of cattle rumen - Thalib A; J Bestari; Y Widiawati; H Hamid; D Suherman (Jurnal Ilmu Ternak dan Veteriner, 2000)
Treatment of rice straw silage with addition of buffalo rumen microbes was conducted to improve the ruminal digestion of rice straw in ongole cattle. Three fistulated cattles were each introduced to dietary treatment: I. Untreated rice straw (JPTP), II. Rice straw ensilaged with buffalo rumen microbes (SJPMR-Kr), and ID. Elephant grass (RG). All diets were formulated isonitrogeneous (14% crude protein) and fed to animals over a period of 4 weeks. After 4 weeks of feeding trial, rwnen fluid of the animals were evaluated to digest its own basal diet (as substrate). The results show that cumulative gas production resulting from the substrate fermented (96 hours) by rumen fluid from cattle fed diet II is 205% of the diet I and 151 % of the diet ID. Measurements of DMD of the substrates after the gas production procedure show the similar trend (ie. DM digestibilities for JPTP= 33%; SJPMR-Kr= 54% dan RG= 45%). Means of in sacco DMD (72 hours incubation) confirm the results of gas production (ie. in sacco DM Digestibilities for JPTP= 35%; SJPMR-Kr= 44% and RG= 39%). All results described between treatments are highly significant different (P<O.OI). Measurements of rumen ecosystems did not show differences between treated animals (P>0.05), except for total VFA (ie. JPTP= 0.52 mg Inri; SJPMR-Kr= 3,37 mg Inri and RG= 3.15 mg Inri).   Key words: Rice straw, silage, microbes, cattle and buffalo